2021
DOI: 10.3390/cancers13040678
|View full text |Cite
|
Sign up to set email alerts
|

Enhance the Immune Checkpoint Inhibitors Efficacy with Radiotherapy Induced Immunogenic Cell Death: A Comprehensive Review and Latest Developments

Abstract: The immunogenic cell death (ICD) is defined as a regulated cell death able to induce an adaptive immunity. It depends on different parameters including sufficient antigenicity, adjuvanticity and favorable microenvironment conditions. Radiation therapy (RT), a pillar of modern cancer treatment, is being used in many tumor types in curative, (neo) adjuvant, as well as metastatic settings. The anti-tumor effects of RT have been traditionally attributed to the mitotic cell death resulting from the DNA damages trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 96 publications
0
35
0
Order By: Relevance
“…Procureur et al. has recently published an excellent review about the enhancement of ICIs by radiotherapy-induced immunogenic cell death ( 157 ). Radiotherapy-induced systemic immune activation could cause shrinkage of distant tumor lesions outside the irradiated field, a phenomenon known as abscopal effect ( 158 ).…”
Section: Novel Strategies To Potentiate Pd-1/pd-l1 Blockade Immunotherapy In Egfr Mutant Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…Procureur et al. has recently published an excellent review about the enhancement of ICIs by radiotherapy-induced immunogenic cell death ( 157 ). Radiotherapy-induced systemic immune activation could cause shrinkage of distant tumor lesions outside the irradiated field, a phenomenon known as abscopal effect ( 158 ).…”
Section: Novel Strategies To Potentiate Pd-1/pd-l1 Blockade Immunotherapy In Egfr Mutant Nsclcmentioning
confidence: 99%
“…Irradiation is known to activate host immunity by triggering ICD, which is characterized by the release of DAMPs to activate dendritic cells and to prime antigen-specific T cells in a dosedependent manner(156). Procureur et al has recently published an excellent review about the enhancement of ICIs by radiotherapy-induced immunogenic cell death(157). Radiotherapy-induced systemic immune activation could cause shrinkage of distant tumor lesions outside the irradiated field, a phenomenon known as abscopal effect…”
mentioning
confidence: 99%
“…Interestingly, very recent data reveal that somewhat similar results may be obtained with conventional RT in combination with DNA repair and immune checkpoint inhibitors [ 501 , 504 , 505 , 506 ] and also with the new evolving technique using high intensity short FLASH IR exposures [ 507 , 508 , 509 , 510 , 511 , 512 ]. Moreover, these approaches were also able to attenuate inflammatory and fibrotic responses as well as the formation of metastasis and secondary cancers.…”
Section: Discussionmentioning
confidence: 82%
“…Conventional radiotherapy and chemotherapy have been attributed to eliciting DNA damage. Emerging evidence has shown that chemoradiation or radiation "boosts" the cancer immunotherapy response (122,123). Radiotherapy has been shown to enhance cancer immunotherapy, leading to more than 100 clinical trials of radiation and immunotherapy combinations across cancer types (124)(125)(126).…”
Section: Radiation and Immunotherapymentioning
confidence: 99%
“…Radiotherapy has been shown to enhance cancer immunotherapy, leading to more than 100 clinical trials of radiation and immunotherapy combinations across cancer types (124)(125)(126). The main rationale of developing cancer radioimmunotherapy is the "boost" of the immune response by radiation via several mechanisms (122). First, due to the intrinsic defects of cancer cells in cell cycle checkpoints, DNA damage checkpoints, DNA replication checkpoints, and mitotic checkpoints (also called spindle assembly checkpoints), irradiated tumor cells with unrepaired and/or incompletely replicated DNA result in cytoplasmic DNA fragments and micronuclei, which activate cGAS/STING signaling.…”
Section: Radiation and Immunotherapymentioning
confidence: 99%